Tingkat Depresi dan Ansietas Pada Usia Produktif - Aldo Evan Wijaya; Elpira Asmin; Lidya B.E. Saptenno (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
The most influential mental disorders are depression and anxiety disorders (anxiety), a major cause of the world's disease burden. The pandemic caused a 27.6% increase in cases of major depressive disorder and a 25.6% increase in cases of anxiety disorders globally. This study aims to find or screen the level of depression and anxiety of productive age. This research method is a descriptive cross-sectional approach by presenting data as a table frequency distribution. The sample in this study used an accidental sampling technique of 27 respondents. The results showed that 25.9% of respondents had mild depression, 14.8% had moderate depression, and the rest were normal. The level of anxiety shows that 11.1% of respondents experience very severe anxiety, 18.5% are in the normal category, and the rest are distributed in the mild to severe anxiety category. In early adulthood, there were 57.1% who experienced depression. The same thing at the age of the early adult respondents was found to experience mild to severe anxiety. It can be concluded that the depression levels of men and women have almost the same percentage. However, the level of mild to very severe anxiety is more experienced by women